Digital Flipbook Empowerment as A Development Means for History Learning Media - A, Muhammad Abror; Suryani, Nunuk; Ardianto, Deny Tri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
The purpose of this research was to help empower the atmosphere and climate of learning students who had different learning styles with the prior generation by using a digital-based instructional media such as digital flipbook. The research methods used were Research and Development, ADDIE model. Data collection obtained through interviews, questionnaires or questionnaires with direct observation. The data analysis technique used was an Independent sample test of hypothesis testing via SPSS version 26. The objects of the research were 11th grade students of Public High School 1 Dagangan, academic year 2019/2020. The results of the research development of digital flipbook learning media on the effectiveness test stage through post-test of the control class and the experimental class showed the mean difference or the average grade of the experimental class (XI Social Sciences 2) 91.6 and grade control (XI Social Sciences 1) 83.5. Thus, digital flipbook learning media that have been developed have succeeded in gaining a significant increase in students' grades as well as succeeding as delivering information media to students in the classroom.